PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF CIVIL AVIATION - Netska Lіubov; Matvieva, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to outline the ways of development of public-private partnership in the field of civil aviation and to formulate proposals for improving the relevant legislation of Ukraine. Research methods: the methods of analysis and synthesis, comparative-legal, systemic-functional and logical-legal were used for the interpretation of normative and legal acts, the study of approaches to legislative regulation and examples of public-private partnership in Ukraine and other countries. Results: the forms of public-private partnership were analyzed and the further expediency of using the concession as the most effective among them for the aviation industry was proven. It was noted the need for changes to the legislation on public-private partnership, in particular the expansion of the spheres of public-private partnership and the definition of the list of objects in the field of aviation for which the use of public-private partnership is possible, implementing the principle of freedom of contract within the framework of public-private partnership, increasing the rights of the investor (private partner), providing state guarantees for the payback of public-private partnership projects, improving the Law of Ukraine «On Concession». Discussion: the need to expand the range of state partners, namely involvement in public-private partnerships as independent state partners of state/municipal enterprises, business associations, institutions; changing the ownership structure of airports and the necessary legislative changes in favor of private partners in terms of their acquisition of ownership rights to objects built within the framework of public-private partnership; feasibility of developing and adopting a separate law on public-private partnership in the field of civil aviation.